Geochemistry of the Volcanic Rocks of the Yüksekova Complex near Güneyköy (SE of Elazığ, E Turkey) - Ural, Melek (My University, 2019)
Some of the volcanic products of the Yüksekova Complex crop out in the Güneyköy (SE Elazığ, E Turkey) area in the SoutheastAnatolian Suture Belt. This study reports the whole rock geochemical data of the volcanics of the Upper Cretaceous YüksekovaComplex around Güneyköy. The volcanic rocks are burgundy and greenish in color. The rocks are massive or have distinct pillowstructure. The volcanic rocks occasionally showing spilitization have basaltic composition and tholeiitic character. The rocks aremainly composed of plagioclases and to a lesser extent clinopyroxene and pseudomorphic olivine minerals. In thin-sections microlyticand hyalomicrolytic porphyritic textures, as well as spherulitic and amygdaloidal textures are common. The secondary minerals arecalcite and epidote. In binary diagrams, the Zr, is considered as immobile and index element; show positive correlation with $Al_2O_3$,$TiO_2$, Nb, Y, Hf, whereas show negative correlation with CaO showing plagioclase, clinopyroxene, olivine and Fe-Ti oxidefractionation during the evolution of the volcanics. N-type mid-ocean ridge basalt-normalized trace element distributions of the rocksamples indicate enrichment in large-ion lithophile elements (LILE) and Th, and negative anomalies in Ta, Nb, Ti and P elements. Thechondrite normalized diagrams of the samples show an approximately parallel and straight trend ($La_N/Sm_N$: 0.93-2.13; $La_N/Lu_N$: 0.23-0.89), suggesting a similar source for the volcanic rocks. The geochemical implications such as negative Nb anomaly, depleted HFSelement abundances and enriched LIL element pattern indicate the contribution of a subducting plate. As a result, the volcanites in thenear of Güneyköy (Elazığ) are members of the Yüksekova Complex and were formed in an intra-oceanic arc environment within theSouthern Branch of Neotethys.
Keywords: Jeokimya ve Jeofizik; Jeoloji; Mineraloji